Developing Students’ Listening Worksheet Of Narrative Text Based On Scientific Approach For Eighth Grade Students At SMP YPI Amir Hamzah Medan - Anisa, Rizki (Universitas Negeri Medan, 2023)
This study focused on developing students’ worksheet for teaching listening skill. The aim of this study was to develop students’ listening worksheet as an additional material for teaching listening skill to the eighth grade students of junior high school. This study was conducted by using Research and Development (R & D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subjects of this study were the eighth grade students at SMP YPI Amir Hamzah Medan. The data were gathered by administering interview to English teacher and distributing questionnaire respondents to get the students’ needs worksheet as a media which can help them to understand about narrative text especially in listening skill. The finding of this study showed that the researcher has developed students’ worksheet that consists of 25 pages with 3 main parts such as the definition of narrative text, the components of narrative text and several exercises that can be used to comprehend the students understanding about narrative text. This worksheet has been validated by two validators, one from State University of Medan and one from SMP Amir Hamzah Medan. This worksheet has the average percentage was 95,5% and it categorized as very good.